Digital Assistant for Medical Management - Maria-Dana-Ștefania CÂMPAN (Applied Medical Informatics)
Currently, in Romania, several solutions exist regarding medical information management and communication between patients and healthcare professionals. However, these solutions have certain limitations in providing centralized access to medical records and ensuring the control over personal medical data.  This study aimed to analyze existing digital healthcare applications and identify their strengths and weaknesses, to propose a more comprehensive approach. The analysis was conducted comparing a few of the major platforms available: Regina Maria, Sanador and MedLife, which are widely used in Romania. Each platform was evaluated based on its functionalities, accessibility, and ability to provide efficient medical management. The results show that Regina Maria’s application focuses on appointment scheduling and access to medical information related to its clinics, also offering an educational section. Sanador provides features similar to Regina Maria, allowing online appointment booking and limited access to medical records, specifically laboratory test results. MedLife, on the other hand, covers a broader network of medical institutions and provides access to test results and consultation scheduling. Despite their benefits, all three platforms lack full integration of patient medical records, and a more direct communication between patients and doctors. To address these gaps, an improved digital healthcare solution should offer centralized medical record management, direct communication with doctors, and expanded functionalities such as automated appointment notifications, access to first aid instructions, e-prescription services, and medication reminders. Additionally, features like an interactive map for locating clinics and pharmacies, a personalized treatment calendar, and a dedicated medical education section would enhance usability. The inclusion of a review system for doctors and clinics would also contribute to better patient decision-making.